A lifetime assessment and prediction method for large area solder joints - Lederer, M.; Kotas, A. Betzwar; Khatibi, G. (Microelectronics and reliability, 2020)
Mechanical bending fatigue experiments were conducted on large area Pb-rich and SnSb-based model solder joints consisting of Cu-strip/solder/DCB substrates. Experimental lifetime curves in the range between 105 and 108 loading cycles at room and elevated temperature showed an improved fatigue resistance for SnSb alloys. Crack length as a function of loading cycles (da/dN) was determined for selected samples to study the cyclic degradation behaviour of the solder layer. Crack initiation and propagation in the joints was modelled on the basis of a damage accumulation rule considering the strain rate and temperature dependency of the solder alloy. Application of the FEM model to large area solder joints allowed calculation of the incremental advancement of the crack front, determination of the crack growth rate (da/dN) and prediction of lifetime under a given loading condition. •High cyclic fatigue life of Pb-rich and SnSb-based model solder joints were determined at room and elevated temperatures•Improved fatigue resistance was obtained for Cu/SnSb solder joints•Strain rate and temperature dependent crack initiation and growth model based on a damage accumulation rule is established•FEM allowed to establish crack growth and life time prediction curves for solder joints under given loading conditions